A search for variability in exoplanet analogues and low-gravity brown dwarfs - Vos, Johanna M.; Henning, Thomas; Homeier, Derek (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. We report the results of a J-band survey for photometric variability in a sample of young, low-gravity objects using the New Technology Telescope (NT